Using acoustic velocities and microimaging to probe microstructural changes caused by thermal shocking of tight rocks - Malenda, Margariete; Vanorio, Tiziana (Frontiers in Earth Science, 2023)
Large scale, Earth processes and bulk rock properties are influenced by underpinning, dynamic, microstructures within rocks and geomaterials. Traditionally, the amount of porosity has been considered the primary control on important bulk rock properties like seismic wave velocities (Vp and Vs) and permeability. However, in tight rocks, velocity and permeability (k) can change substantially despite small changes in the amount of porosity during cracking. Therefore, other microstructural features inherent to given lithologies, such as heterogeneity and anisotropy in mineral properties are considered as factors controlling these bulk rock properties. Understanding which microstructural features control Vp, Vs, and permeability in tight rocks is useful in applications like enhanced geothermal systems (EGS), where thermal shocking is used to increase permeability. Thermal shocking involves injecting surface water into the subsurface to cool mineral crystals, induce contraction of crystals, and cause thermal cracking. We tested three tight lithologies with unique microstructures; granodiorite (SWG), basalt (PTB), and carbonate (MSA). We simulated thermal shocking by slowly heating samples to 350°C and then quenching them. We chose a temperature of 350C because thermal shocking at this temperature is not well documented in literature, and this temperature is relevant to EGS. Using time-lapse microimaging, we assessed how thermal cracking occurs in each lithology and explored how thermal cracks influence connected porosity, Vp, Vs, and k. Microimaging shows extensive cracking in the SWG and MSA lithologies, and little to no cracking in PTB with thermal shocking treatment. Vp and Vs became more pressure sensitive, and elastic moduli decreased with treatment for all lithologies. This may be caused by reduced stiffness between mineral crystal boundaries with treatment. Lithologies with minerals that have anisotropy of or a wide range in thermal conductivity and/or thermal expansion coefficients can have increased thermal cracking. In thermally shocked SWG and MSA, Vp and Vs are good indicators of thermal cracking and k increases, but less so in PTB. Lithologies like PTB may require multiple thermal shock stimulations to increase permeability. Our results highlight how micro-scale changes influence bulk rock properties and when we can monitor permeability increases and microscale thermal cracking with Vp and Vs.